Corona Detection Using Wide Band Antenna and Time Delay Method - A. A. Raj; S. Ishak; M. D. M. Amir; B. Yogendra; M. Raffi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
IEEE Std 100-2000 defines corona as a luminous discharge due to ionization of the air surrounding a conductor caused by a voltage gradient exceeding a certain critical value. It occurs when the insulating material begins to ionize or conduct due to voltage stress. Corona brings a lot of damages such as corrosion, loss inoverhead transmission lines and electromagnetic interference. Monitoring of corona may reduce the maintenance and replacement cost of electrical equipment. The motivation of this experiment is to calibrate corona detector antennas in the future. The error obtained will determine the efficiency of the antenna to detect and locate potential coronas in electrical equipment in a substation with switchgears or transformers. The operation bandwidth of the antenna is 320MHz to 1.20GHz making it useful to detect and corona. The measurement method of utilizing delay between signals first peak is effective with average 4.76% error with maximum 10.0% error recorded. This may be used to develop a corona online measuring system in the future.